Teacher's Perspective Towards Plurilingualism and Its Influence on English Academic Achievement and Language Learning Styles - Na’imah Na’imah (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Plurilingualism gives confidence that a person can have the competence of more than one language to switch between several languages depending on the situation for ease of communication. The study of pluringualism is closely related to English which is the second language in Indonesia. This of course is also related to learning English. So, because of that, this study aims to know the teacher's perspective on Plurilingualism and its effects on the achievement of academic English and the style learn children's language good from aspect quantitative or qualitative. With methodology used is through method mixture or what is called with mix methods with taking sample study student fifth and sixth-grade school Ibtidaiyah Elementary and Madrasah ages 10 to 12 years. With data collection techniques through questionnaires and interviews. Based on the results of research and calculations that earned level significance (1-tailed) 0.095 > 0.05, that could conclude that teacher's perspective on plurilingualism has a connection and influence on the achievement of children's academic and language learning style, especially in English learning at school. So, by giving attention to the results of this study, teachers should believe that each child has the competence of more than one language to switch between several languages. That way it will be able to affect children's English learning outcomes to be more optimal.